Prescribing of Strong Opioid Analgesics by UK Primary Care Physicians from 2000 to 2010 - Zin, Che Suraya; Chen, Li-Chia; Knaggs, Roger D (John Wiley & Sons, 2012)
Background: An increasing trend in opioid prescribing over the past 10 years has been reported, and this trend was associated with increasing incidences of dependence and misuse, healthcare resources consumption and death rate in the United States. However, little is known about the opioids prescribing in primary care settings in the United Kingdom (UK). Objectives: This study evaluated the utilisation trends of strong opioid analgesics prescribed for pain management in the UK primary care settings. Methods: This cross-sectional study was conducted from 2000 to 2010 using the General Practice Research Database, which is a large computerized health care database collected from 639 primary care practices throughout the UK. Prescribing data of patients who were prescribed strong opioid-containing drugs (buprenorphine, fentanyl, morphine and oxycodone) for pain management were extracted by using specific product codes. Total number of prescriptions for each drug was calculated. Descriptive statistics and simple linear regression were used to evaluate the proportion and annual trend of number of prescriptions. Results: A total of 2.77 million prescriptions were identified for study drugs over the 11 years study period. Of those prescriptions, morphine was the most frequently prescribed category (n = 1.39 million, 50%), followed by fentanyl (n = 487,771, 18%), buprenorphine (n = 474,869, 17%) and oxycodone (n = 424,126, 15%). The trends of prescribing for all study drugs significantly increased (p < 0.001) from 2000 to 2010. Prescribing of oxycodone increased the most (10,960%) compared with buprenorphine (1,707%), fentanyl (1,135%) and morphine (394%). Conclusions: This preliminary study showed that the prescribing trend for strong opioid analgesics in the UK has increased significantly in the past 11 years. Further studies are required to understand the reasons for the increasing prescribing trend, quantify the opioid prescribing doses and test the association between increasing opioid utilisation and clinical outcomes.